The effects of hydroxyurea derivative 1, 3, 4- thiadiazoles on serum biochemical parameters and antioxidant status in liver of rats - Karagozoglu, Yusuf; Türko?lu, Semra; Parlak, Akif E.; Alayunt, Naci Ö. (Inst Materials Physics, 2013)
In this study, it was aimed to investigate the antioxidant and antihepatotoxic effect of hydoxyurea derivative 1,3,4-thiadiazoles on serum biochemical parameters (AST, ALT, LDH, urea, creatinine and total bilirubin) and antioxidant parameters (SOD, CAT, GPX, MDA). In our study, a total of 35 adult male wistar rats were divided into 5 equal groups. DMSO diluted with only corn oil, was injected to the control group. 25 mg/kg ligand, 25 mg/kg thiadiazole-manganese, 25 mg/kg thiadiazole-cadmium and 25 mg/kg thiadiazolechrome complexes was injected to the experimental groups rats subcutaneously for 15 days with three-day interval during the test. After blood samples were centrifuged AST, ALT, LDH enzyme activites hepatic injury; and then, the activites of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), and the level of malondialdehyde (MDA) in liver tissues were determined spectrophotometrically. The level of AST was found to be lower (p<0.05) in the Cr-L group than in other groups. The levels of ALT and total bilirubine were found to be lower (p<0.05) in the Cd-L group than in other groups. The level of SOD was found to be higher (p<0.05) in the Cd-L group than in other groups. The levels of GPX was found to be lower (p<0.05) in the Cr-L group than in other groups. As a result, it can be concluded that their pharmacological characteristics can be beneficial in many fields of application because hydroxyurea derivative 1,3,4 thiadiazole compounds show the antioxidant and antihepatotoxic activity.
Keywords: Antioxidant status; Biochemical parametres; Hydroxyurea; Liver; Serum; Thiadiazoles